Transgender Intimate Partner Violence : A Comprehensive Introduction - Xavier L., Guadalupe-DiazXXecontributorXX4ctbXX4https://id.loc.gov/vocabulary/relators/ctb; Xavier L., Guadalupe-XXecontributorXX4ctbXX4https://id.loc.gov/vocabulary/relators/ctb; Walter S., DeKeseredyXXecontributorXX4ctbXX4https://id.loc.gov/vocabulary/relators/ctb; Taylor, FlaggXXecontributorXX4ctbXX4https://id.loc.gov/vocabulary/relators/ctb; Sharyn J., Potter; Sharyn J., Potter; Shanna K., Kattari; Shanna K., Kattari; Rebecca, Howard; Rebecca, Howard; Rayna E., Momen; Rayna E., Momen; et al. (Book collections on Project MUSE., 2020)
A groundbreaking overview of transgender relationship violenceIn the course of their lives, around fifty percent of transgender people will experience intimate partner violence in their relationships-including psychological, physical, or sexual abuse. In Transgender Intimate Partner Violence, Adam M. Messinger and Xavier L. Guadalupe-Diaz bring together a diverse group of scholars, service providers, activists, and others to examine this widespread problem, shedding light on the often-hidden experiences of transgender survivors. Drawing on two decades of research, contributors explore transgender intimate partner violence in all of its complexities, offering an overview of this emerging body of policy, research, and practice. They offer best practices to enhance research, services, and healing for transgender survivors. A revolutionary volume, Transgender Intimate Partner Violence offers insight into how to create a compassionate and inclusive world for transgender communities.